Financial Inclusions : A study on Agent Banking - Amir, Md Khaled Bin (Dhaka University Journal of Business Studies, 2021)
The main purpose of this research is to reflect the attainment of financial involvement through agent banking. Trend analysis of number of accounts, amount of deposits, loans and amount of remittances flow have illustrated the positive growth of agent banking both in countryside and urban areas during 2015 to 20120.Both the Pooled OLS and random effect model demonstrate the significant impact of amount of deposits and remittances flow in agent banking of Bangladesh. Hausman test supports random effect model over fixed effect at showing the effect on deposit to number accounts but opposite results have been observed to show the effect on remittances to number of accounts. Breusch and pagan lagrangian multiplier test elucidated that OLS is better than random effect model. The data set is free from multicollinearity but variances are not constant which means heteroscedasticity problem exists. Ramsey RESET test proves the model has omitted variable bias due to insufficiency of relevant variables’ data over the consecutive years. Journal of Business Studies, Vol. XLII, No. 1, April 2021 Page 1-15